Harnessing traditional principles and guidelines for utilization compliance and sustainability of Maasai Alalili systems in northern Tanzania - Elkana Hezron; Issakwisa B. Ngondya; Linus K. Munishi (Sustainable Environment)
Resilience in Indigenous communities and their lands faces challenges from multiple fronts, including climate change, biodiversity loss, altered biogeochemical flows, and socio-cultural transitions. Innovative solutions like Indigenous local knowledge featuring the community repositories that could enable policy practice are needed to explore, shift, and articulate such trajectories towards sustainable and desired futures. The study used a mixed-method approach to gather information on the extent to which Maasai communities practice traditional principles and guidelines for sustainable management of the Alalili systems. Purposive and stratified random sampling techniques facilitated data collection from literature review, direct field observation, key informant interviews, focused group discussions, and household surveys, which were analyzed using Chi-square and t-tests, narrative, and descriptive techniques. The findings indicate a variation between the traditional principles and guidelines reported from the surveyed literature and those recorded from the field survey. We found that the literature sparingly reported six aspects of the traditional principles and guidelines, whereas the field survey from the community comprehensively reported four harmonized aspects. More than 50% of the surveyed Alalili systems are currently not complying with documented management principles and guidelines from the literature and community traditions, thus increasing their proximity to the effects of degradation. We reveal that the probability of compliance is higher in the private Alalili category. We recommend their official recognition by policymakers and putting them into practice as a conservation initiative for supporting future rangeland sustainability and the pastoral communities’ livelihood development.